The Characters’ Solicitude in Tere Liye’s Novel Negeri Di Ujung Tanduk - Hariani, S; ., Pardi; Siregar, A; ., Asnani (KnE Social Sciences, 2018)
This study aims to describe the characters’ solicitude in the novel Negeri di Ujung Tanduk by Tere Liye. Tere Liye through the novel portrays about the solicitude which showed by the characters. This study is supported by Bender’s theory (2003) about the solicitude. It is stated that solicitude is to make ourselves related to others and whatever happens to that person. People who prioritize the needs and feelings of others rather than their own interests are caring people. They will not hurt other people’s feeling. Many values that contained in the solicitude such as kindness, generosity, attention, helping and compassion. This study is conducted by using descriptive qualitative method by Miles and Huberman (1994). The data used are the sentences and paragraphs which show the characters’ solicitude contained in the novel. The result of the study shows that there are some values which contained in the solicitude among the characters; they are kindness, generosity, caring, helping and compassion. Keywords: solicitude, kindness, generosity, caring, helping, compassion